Chaucer 1340-1400 : the life and times of the first English poet - West, Richard, 1930- (New York : Carroll & Graf, 2002)
"Richard West weaves a fascinating picture of an age in his quest to reveal the nature of this extraordinary man, whose own character has always puzzled lovers of his comic masterpiece, The Canterbury Tales.
As a child he survived the Black Death, later he fought in France during the Hundred Years War, served as a diplomat in Italy during the turmoil leading up to the papal schism, and became a Member of Parliament at the angry beginnings of the Protestant Reformation, the bloody Peasants' Revolt and the overthrow and murder of Richard II. The book begins and ends in Canterbury, the scene of Becket's martyrdom and a focal point of English history for more than two thousand years."--BOOK JACKET.
1. Canterbury Pilgrims -- 2. Edward III goes to War -- 3. The Rise of the English Merchants -- 4. The Black Death: Chaucer and the Jews -- 5. The Black Death: Why it was Soon Forgotten -- 6. Chaucer as Schoolboy and Soldier -- 7. The Romance of the Rose -- 8. Chaucer in Florence -- 9. Chaucer in Lombardy -- 10. Wyclif and the Friars -- 11. The Peasants' Revolt -- 12. Troilus: War and Chivalry -- 13. Troilus: Chaucer and the Novel -- 14. The Knight's Tale -- 15. The Wife of Bath on Women and Marriage -- 16. A Trueborn Englishman.
Includes bibliographical references and index.
Keywords: Chaucer, Geoffrey, -- -1400 -- Biography; Poets, English -- Middle English, 1100-1500 -- Biography